The G-protein Coupled Receptor GPR8 Regulates Secondary Metabolism in Trichoderma reesei - Hinterdobler, Wolfgang; Beier, Sabrina; Monroy, Alberto Alonso; Berger, Harald; Dattenböck, Christoph; Schmoll, Monika (Frontiers in Bioengineering and Biotechnology, 2020)
Changing environmental conditions are of utmost importance for regulation of secondary metabolism in fungi. Different environmental cues including the carbon source, light and the presence of a mating partner can lead to altered production of compounds. Thereby, the heterotrimeric G-protein pathway is of major importance for sensing and adjustment of gene regulation. Regulation of secondary metabolism is crucial in the biotechnological workhorse Trichoderma reesei for knowledge-based adjustment in industrial fermentations, but also with respect to the potential use as a host for heterologous compound production. We investigated the function of the class VII G-protein coupled receptor (GPCR) gene gpr8 that is localized in the vicinity of the SOR cluster, which is responsible for biosynthesis of sorbicillinoids. GPR8 positively impacts regulation of the genes in this cluster in darkness. Accordingly, abundance of trichodimerol and dihydrotrichotetronine as well as other secondary metabolites is decreased in the deletion mutant. Transcriptome analysis moreover showed the major role of GPR8 being exerted in darkness with a considerable influence on regulation of secondary metabolism. Genes regulated in Δgpr8 overlap with those regulated directly or indirectly by the transcription factor YPR2, especially concerning genes related to secondary metabolism. The predicted FAD/FMN containing dehydrogenase gene sor7, one of the positive targets of the cascade triggered by GPR8, has a positive effect on secondary metabolite production, but also cellulase gene expression. Hence SOR7 has some overlapping, but also additional functions compared to GPR8. The G-protein coupled receptor GPR8 exerts a light dependent impact on secondary metabolism, which is in part mediated by the transcription factor YPR2 and the function of SOR7. Hence, T. reesei may apply GPR8 to adjust production of secondary metabolits and hence chemical communication to signals from the environment.